THE URGENCY OF TEACHING PRACTICES ON PROSPECTIVE TEACHERS’ TEACHING ABILITY - Rahmi Rahmawati; Eva Latipah; Ghulam Murtadlo (Jurnal Eduscience, 2023)
Education is a kit for a person to free from the shackles of ignorance, poverty, and underdevelopment. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students. Teaching practice is an effort to demonstrate the competence of prospective teachers in planning, carrying out learning and assessing the effectiveness of learning. This study aims to determine the urgency of teaching practice on the teaching abilities of prospective teachers. The research method is using literature study. The results of the study show that teaching practice is one of the most important, because practice means conducting real experiments and during the experiment a practitioner pays attention to the ongoing process until finally knowing something is lacking and then trying to fix it. Teaching practice is carried out as an implementation of improving the teaching and learning process in the classroom. Teaching practice is something urgent that must be carried out by every student teacher candidate, because it trains them so that they have the ability to demonstrate performance in real situations in learning activities in educational institutions in the future.